ExpI and PhzI are descendants of the long lost cognate signal synthase for SdiA. - Anice Sabag-Daigle; Brian M M Ahmer (PLoS ONE, 2012)
SdiA of E. coli and Salmonella is a LuxR homolog that detects N-acyl homoserine lactones (AHLs). Most LuxR homologs function together with a cognate AHL synthase (a LuxI homolog), but SdiA does not. Instead, SdiA detects AHLs produced by other bacterial species. In this report, we performed a phylogenetic analysis of SdiA. The results suggest that one branch of the Enterobacteriaceae obtained a rhlR/rhlI pair by horizontal transfer. The Erwinia and Pantoea branches still contain the complete pair where it is known as expR/expI and phzR/phzI, respectively. A deletion event removed the luxI homolog from the remainder of the group, leaving just the luxR homolog known as sdiA. Thus ExpR and PhzR are SdiA orthologs and ExpI and PhzI are descendants of the long lost cognate signal synthase of SdiA.